Measuring Firm Activity from Outer Space - Katarzyna Anna Bilicka; André Seidel (Center for Economic Studies and ifo Institute (CESifo), 2022)
To understand how global firm networks operate, we need consistent information on their activities, unbiased by their reporting choices. In this paper, we collect a novel dataset on the light that factories emit at night for a large sample of car manufacturing plants. We show that nightlight data can measure activity at such a granular level, using annual firm financial data and high-frequency data related to Covid-19 pandemic production shocks. We use this data to quantify the extent of misreported global operations of these car manufacturing firms and examine differences between sources of nightlight.
Keywords: H32; H26; F23; 330; multinational firms; nightlight data; global firm networks